Bile Microbiome in Patients with Recurrent Common Bile Duct Stones and Correlation with the Duodenal Microbiome - Jungnam Lee; Jin-Seok Park; Jaewoong Bae; Sohee Lee; Yeonju Hwang (Life, 2022)
Background: Common bile duct (CBD) stone recurrence is a common late adverse event after CBD stone treatment. In this preliminary study, we compared the bile fluid and duodenum microbial profiles of patients with or without recurrent CBD stones to identify risk factors associated with recurrence. Methods: Bile fluid samples of 47 consecutive patients who underwent ERCP for biliary diseases were subjected to microbiome analysis. Nineteen patients were stone-recurrent (SR), and 28 patients were non-stone-recurrent (NSR). Paired samples (duodenum biopsy tissue and bile fluid samples) from five SR patients were used to compare microbiome compositions in the biliary system and duodenum. In addition, we compared the microbiome compositions of these duodenal tissue samples with those 12 controls (gastric ulcer patients without recurrent CBD stones). Results: Enterococcaceae_unclassified and enterococcus were more abundant in bile fluid in the SR group than in the NSR group (p = 0.002 and p = 0.003, respectively). A comparison of the microbiome compositions of duodenum tissue and bile fluid samples of the five recurrent CBD stone patients revealed proteobacteria compositions were almost identical from the phylum to genus level. In these five patients, alpha and beta diversities were no different in bile fluid and duodenal tissues. Furthermore, a comparison of the microbiome compositions of duodenal mucosa in patients with recurrent CBD stone patients (n = 5) and controls (n = 12) revealed significant differences between microbiome compositions. Conclusions: Enterococcus seems to contribute to CBD stone development. Furthermore, our results indicate that retrograde migration of the duodenal microbiome may contribute to bile microbiome alterations. We recommend that more research be conducted to confirm this hypothesis.